2020
DOI: 10.1038/s41598-020-60683-2
|View full text |Cite|
|
Sign up to set email alerts
|

The hemodynamic complexities underlying transient ischemic attacks in early-stage Moyamoya disease: an exploratory CFD study

Abstract: Moyamoya disease (MMD) is a rare cerebro-occlusive disease with unknown etiology that can cause both ischemic and hemorrhagic stroke. MMD is characterized by progressive stenosis of the terminal internal carotid artery (ICA) and development of basal brain collaterals. Early-stage MMD is known to cause hemodynamic insufficiency despite mild or moderate stenosis of the intracranial arteries, but the exact mechanism underlying this pathophysiological condition is undetermined. We used highresolution Large eddy Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…This interaction causes and modulates many vascular pathologies such as stenosis, aneurysms, and atherosclerosis 16,24,25 . We have previously shown that MMD symptomatology is impacted by complex hemodynamics arising from the complex morphology of the MMD associated ICA stenosis in early stage MMD 26 . However, our previous work does not provide a causal link between vascular hemodynamics and MMD initiation, but it was rather focused on the impact of MMD induced ICA stenosis on the hemodynamics leading to transient ischemic attacks (TIA).…”
Section: Results: ➢ Rnf213 Is a Mechano-responsive Gene That Regulates Endothelial Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction causes and modulates many vascular pathologies such as stenosis, aneurysms, and atherosclerosis 16,24,25 . We have previously shown that MMD symptomatology is impacted by complex hemodynamics arising from the complex morphology of the MMD associated ICA stenosis in early stage MMD 26 . However, our previous work does not provide a causal link between vascular hemodynamics and MMD initiation, but it was rather focused on the impact of MMD induced ICA stenosis on the hemodynamics leading to transient ischemic attacks (TIA).…”
Section: Results: ➢ Rnf213 Is a Mechano-responsive Gene That Regulates Endothelial Angiogenesismentioning
confidence: 99%
“…A very interesting aspect of MMD is the exclusive occurrence of stenosis in the carotid terminus, despite being a genetic disease that, theoretically, should impact many vessels in the body. A way to explain this phenomenon is by looking at the blood hemodynamics in MMD patients 26 . However, traditional analysis methods utilizing wall shear stress or other common parameters fail to pinpoint the causality of MMD locality of pathogenesis 24,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason is that the deconvolution process is sensitive to AIF selection 23 . It is highly challenging for clinicians to select the optimal AIF at any DSC MRI scans consistently given the hemodynamic complexities in MMD 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulation has been successfully used to evaluate hemodynamic quantities in the major arteries of the CoW 8, 12, 13 . As variations in vessel architecture can strongly influence local hemodynamics including WSR 14 , it is critically important that computational modeling accurately captures a patient’s vascular anatomy.…”
Section: Introductionmentioning
confidence: 99%